Manajemen Pengelolaan Samsara Living Museum Sebagai Daya Tarik Wisata Budaya Di Desa Jungutan, Kecamatan Bebandem, Kabupaten Karangasem - Putri, Ida Ayu Karina; Putri, Komang Shintiya Nita Kristiana (JURNAL DESTINASI PARIWISATA; Vol 10 No 2 (2022): VOL 10, NO 2 (2022): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i02.p15, 2022)
Karangasem Regency has a very varied topography such as plains, hills and mountains. Through the image of the destination "Karangasem, The Spirit of Bali", Karangasem Regency has a vision and mission to preserve and introduce the existence of authentic Balinese values. Strengthening the image of destinations in Karangasem Regency is carried out through the development of the Samsara Living Museum of Life because this museum is not limited to mere physical space but interprets the noble values of Balinese people such as rituals, traditions, culture, and local wisdom. This study uses a qualitative method. Data collection uses several methods such as interviews, observation and documentation. This research using key person as the informant. The results show Samsara Living Museum puts forward activities related to the preservation of Balinese art and culture. The implementation of management at the Samsara Living Museum consists of preserving cultural heritage assets, such as heirlooms, historical manuscripts and literacy, art and culture packaging, building basic facilities, and building community business units. Keywords: Operation Management, Karangasem Regency and Samsara Living Museum